(untitled) (Journal of Solar Energy Research Updates, 2014)
Proper installation, especially the tilt angle, directly affects the system’s output. Determination of the optimal tilt angle of a solar cell module depends on the solar radiation characteristics, season, and reflectivity in the local area. One of the important parameters that affect the performance of a solar collector is its tilt angle with the horizon. This is because of the variation of tilt angle changes the amount of solar radiation reaching the collector surface. A mathematical model is presented for determining the optimum tilt angle at different orientations (surface azimuth angle) for the solar collector, on a daily basis, as well as for a specific period such as monthly, seasonally and yearly basis. The optimum angle was computed by searching for the values for which the extraterrestrial solar radiation on the collector surface is a maximum for a particular day or a specific period. The results reveal that changing the tilt angle 12 times in a year (i.e. using the monthly optimum tilt angle) or even 4 times/year (i.e. using the seasonally optimum tilt angle) maintains approximately the total amount of solar radiation near the maximum value that is found by changing the tilt angle daily to its optimum value. This achieves a yearly gain in solar radiation of 5.5% at 0o latitude to 78% at 60o latitude more than the case of a solar collector fixed on a horizontal surface.